Exploring the Role of the Behavioral Immune System in Acceptability of Entomophagy Using Semantic Associations and Food-Related Attitudes - Qian, Kun; Yamada, Yuki (Frontiers in Nutrition, 2020)
Entomophagy refers to eating insects. Insect food, including cooked insects and other processed food with insect-based ingredients, is consumed in many regions of the world as a part of traditional dietary behavior, or as innovative functional food. However, many people especially in western or industrialized societies have shown negative attitudes such as resistance or disgust to entomophagy. In this study, we examined the acceptability of eating insects from the context of the behavioral immune system (BIS), by employing a questionnaire survey and picture-based semantic association experiment. We collected data from 1369 Japanese participants (581 females and 788 males, mean age = 43.41 years, SD = 10.44 years) by conducting an online survey. The results revealed the influence of the behavioral immune system on entomophagy: The semantic associations between insect food and non-insect food, and between insect food and pathogens were significantly predicted by multiple domains related to the attitudes, concerns, and experience of food and pathogens. The semantic associations between insect food and pathogens were significantly stronger than other associations. People who concentrate on food safety and hygiene revealed fewer associations between insect food and non-insect food. These results indicated that promoting the sanitary and hygienic image of insect food may reduce revulsion at entomophagy and promote uptake.